Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1590/0103-6440202103700
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Discoloration Using Calcium Silicate-Based Cements For Simulated Revascularization in Vitro

Abstract: The endodontic revascularization may be an alternative treatment for necrotic immature teeth, however, several treatment steps may cause tooth discoloration. This study evaluated the use of three calcium silicate-based cements with different radiopacifying agents on the color alteration (∆E) of extracted premolars after simulation of revascularization. Forty single rooted extracted premolars were shaped with #1-6 gates Glidden drills, rinsed with sodium hypochlorite, and filled with fresh human blood. Three ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…In another study using bovine teeth, Marciano et al [ 5 ] found that teeth filled with Portland cement that have different radiopacifiers other than bismuth oxide (zirconium oxide and calcium tungstate) have exhibited color stability, and no color change have occurred after zirconium oxide and calcium tungstate were placed in contact with collagen, but, discoloration was observed when the authors placed bismuth oxide in contact with the collagen [ 31 ]. Similar findings have been reported more recently demonstrating again that, calcium silicate cement containing bismuth oxide was found to cause the highest color change compared to those with zirconium oxide or calcium tungstate as radiopacifiers when the cements were placed into extracted human premolars in contact with blood [ 32 ].…”
Section: Discussionsupporting
confidence: 87%
“…In another study using bovine teeth, Marciano et al [ 5 ] found that teeth filled with Portland cement that have different radiopacifiers other than bismuth oxide (zirconium oxide and calcium tungstate) have exhibited color stability, and no color change have occurred after zirconium oxide and calcium tungstate were placed in contact with collagen, but, discoloration was observed when the authors placed bismuth oxide in contact with the collagen [ 31 ]. Similar findings have been reported more recently demonstrating again that, calcium silicate cement containing bismuth oxide was found to cause the highest color change compared to those with zirconium oxide or calcium tungstate as radiopacifiers when the cements were placed into extracted human premolars in contact with blood [ 32 ].…”
Section: Discussionsupporting
confidence: 87%
“…The most common method for color change evaluation was spectrophotometry, used in six studies [12,13,21,27,41,42], followed by spectrophotometry used with a digital camera [14,24,25,28,40], colorimetry [22], spectroradiometry [23], and only a digital camera [26].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Color changes were measured by calculating ∆E values in all studies. Eleven publications [12][13][14]21,22,[24][25][26]28,40,42] indicated human eye perceptible color change ranging from ∆E1.2 to ∆E3.7, whereas three articles [23,27,41] did not provide numeric information about ∆E thresholds, which were taken as perceptible to the human eye.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor related to coronary discoloration following REP is the use of calcium silicate-based cervical barriers 1,7,9,10,[12][13][14][15] and their interaction with the blood clot 16 , especially those that have bismuth oxide in their composition, which when in contact with collagen matrix result in a darkened precipitate 13 .…”
Section: Introductionmentioning
confidence: 99%